Geology of Byobu Rock and Gobanme Rock, Prince Olav Coast, East Antarctica - Satish-Kumar, M.; Kagashima, Shin-ichi; Suda, Yoshimitsu; Motoyoshi, Yoichi (National Institute of Polar Research, 2006)
P(論文) We report here the geology of Byobu Rock and Gobanme Rock outcrops hitherto unmapped in the Prince Olav Coast, East Antarctica. Both these outcrops expose high-grade metamorphic and igneous rocks. The metamorphic rock units comprise mainly of gneisses migmatized to variable extent and amphibolites, whereas igneous rocks comprise of granites and pegmatites. Preliminary structural data obtained from the outcrops identified the regional, steep to moderately dipping foliation trend in the WNW-ESE at Byobu Rock, whereas they trend in the NW-SE direction at Gobanme Rock. Two generations of folding were identified, an earlier tight isoclinal intrafolial folds and a late regional open fold. The three deformational events identified are comparable and consistent with those reported in the neighboring outcrops in the Prince Olav Coast. Metamorphic P-T conditions estimated based on various geothermobarometries indicate that the rocks have experienced granulite grade conditions during peak metamorphism (770-880°C and 6-9kbar). The finding of orthopyroxene at Byobu Rock in this study extends the orthopyroxene-in isograd in the progressive metamorphic zone in the Lutzow-Holm Complex further eastward beyond Tenmondai Rock. Inclusions of kyanite within garnet in metapelitic rocks suggest a clockwise P-T path, consistent with the P-T paths suggested for the Lutzow-Holm Complex. Preliminary bulk rock geochemical investigations indicate that granitic rocks and quartzo-feldspathic gneiss mostly belong to volcanic arc granite suite, though their origin remains indistinct. Electron microprobe dating of monazites from representative rocks gave Pan-African ages (557±33Ma), consistent with the regional metamorphic ages reported earlier. Thus, based on the similarities on structural, petrological, geochemical and geochronological data, the Byobu Rock and Gobanme Rock are considered to be integral part of the Pan-African Lutzow-Holm Complex with analogous geological history. departmental bulletin paper